The Image of God and Human Uniqueness: Challenges from the Biological and Information Sciences. (October 2015) - Burdett, Michael S.
The image of God is the doctrinal home of human uniqueness. Indeed, the Genesis text indicates that the image of God is decisively what separates human beings from the rest of creation and helps to define the human being as a special creature in the order of creation. Recent work in the biological and information sciences is eroding the centuries-old conviction that we are unique as creatures. How does this affect how we understand the image of God? Should we experience this loss of human uniqueness as damaging to the Christian faith? These questions are addressed by first calling attention to the various ways the image of God have been interpreted throughout Christian history. Employing the four views of the image of God—substantive, functional, relational and dynamic—I argue that this loss of human uniqueness need not threaten the image of God in each of these cases, but rather helps provide clarity to the doctrine itself.